2015
DOI: 10.1111/hpb.12487
|View full text |Cite
|
Sign up to set email alerts
|

Post‐embolization syndrome as an early predictor of overall survival after transarterial chemoembolization for hepatocellular carcinoma

Abstract: PES is a common complication after TACE and is associated with a two-fold increased risk of death. Future studies should incorporate PES as a relevant early predictor of OS and examine the biological basis of this association.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
41
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(49 citation statements)
references
References 47 publications
1
41
0
Order By: Relevance
“… 3 , 19 , 20 Prognosis was even worse in patients who developed severe complications after TACE. 21 In our study, the 3-year overall survival probability was 37.74% in the JLD group and 26.00% in the control group. The results of survival analysis in our study suggested that the JLD group had a significantly higher 3-year overall survival probability than the control group ( P =0.0365 by log-rank test).…”
Section: Discussionsupporting
confidence: 43%
“… 3 , 19 , 20 Prognosis was even worse in patients who developed severe complications after TACE. 21 In our study, the 3-year overall survival probability was 37.74% in the JLD group and 26.00% in the control group. The results of survival analysis in our study suggested that the JLD group had a significantly higher 3-year overall survival probability than the control group ( P =0.0365 by log-rank test).…”
Section: Discussionsupporting
confidence: 43%
“…Moreover, in a recent study, (8) the occurrence of PES was associated with worse survival after TACE. (8) Because this study was retrospective and was not designed with adequate stratification, the findings cannot be considered conclusive; nonetheless, this suggestion cannot be ignored given the potential detrimental effects of cytokines released during PES. Hence, a safe and effective prevention of PES occurrence after endovascular treatments for HCC would be of great benefit for the medical community, and most importantly for patients' quality of life.…”
mentioning
confidence: 89%
“…However, PES is not only an inconvenience for patients—which occasionally discourages subsequent TACE courses due to the threat of recurrence—but it often prolongs hospital stays, causes diagnostic dilemmas in case of fever and pain leading to additional diagnostic testing, and is therefore a burden for physicians and administrators. Moreover, in a recent study, the occurrence of PES was associated with worse survival after TACE . Because this study was retrospective and was not designed with adequate stratification, the findings cannot be considered conclusive; nonetheless, this suggestion cannot be ignored given the potential detrimental effects of cytokines released during PES.…”
mentioning
confidence: 89%
“…Third, we did not assess the relationship between the long-term outcomes of HCC patients and post-TACE pain. Although a previous study reported that postembolization syndrome is an early predictor of poor overall survival for patients with advanced and unresectable HCC, 29 the relationship between post-TACE pain and overall survival has not been well studied. We believe this correlation needs to be further studied and characterized.…”
Section: Discussionmentioning
confidence: 99%